PENGARUH PENDAPATAN PREMI TERHADAP LABA PADA AJB BUMIPUTERA 1912 CABANG BANDUNG SETIABUDHI - Marlina, Lina; Hidayat, Agi Syarif (Jurnal Ecodemica, 2013)
ABSTRACT - Every companyin theactivityaims togenerateprofits, buta phenomenon that occursinAJBBumiputerashoweda decline incorporate profits.The purposeofthis studyis to describethe premium revenue, profitpictureandtoknow how to influencetheearningspremium incomeonAJBBumiputera1912BandungBranchSetiabudhi. Researchmethodsthat will beusedis descriptiveand and verificationmethodswith case study approach. The statistical methods usedtoanalyze the effect ofindependent variables onthedependent variableis theprodutmomentcorrelationtechnique, the coefficientof determination, and at test. Data usedin this studyisdirectlyfrom theobjectof research. Hypothesis testingwillbe doneby usinga significance levelof 0.05(Î± =0.05) or theconfidence levelof 0.95. Resultsof the study showthat thepremium incomeandprofitonAJBBumiputera 1912BandungBranchSetiabudhiexperiencingfluctuatinggrowth. Based on the analysis, the hypothesisinthis study receivedthepremium incomeaffectprofitabilityofcompanieswithstrong category0,622. Coefficient of determinationofthe regressionequationis equal to0,438. It meanspremiumpendpatanvariable(X) hascontributed toincome(Y) of 43,8%. While the remaining100% - 43,8% =56,2% influencedbyother factors. Keywords: Income, Premiums, TheCompany andProfits